Multi-omics and AI-driven advances in miRNA-mediated hair follicle regulation in cashmere goats - Chunhua, Zhang; Le, Fu; Shengli, Li; Sachula, Wu; Bao, Hua; Lan, Mu; Antonini, Marco; Haizhou, Sun (Frontiers in Veterinary Science, 2025)
Hair follicle development and cycling are governed by intricate genetic and molecular networks, with microRNAs (miRNAs) playing essential roles as post-transcriptional regulators. In cashmere goats, valued for their fine fiber, miRNAs have emerged as key modulators influencing hair follicle morphogenesis, regeneration, and fiber traits such as fineness and pigmentation. This review highlights recent discoveries in miRNA-mediated regulation of hair follicles, focusing on their dynamic expression patterns and cell-specific functions in keratinocytes, dermal papilla cells, and follicular stem cells. Key miRNAs, including miR-31, miR-22, and miR-214, are explored for their effects on follicle growth, hair shaft formation, and pigment regulation. We discuss advances in single-cell RNA sequencing and spatial transcriptomics, revealing new insights into cellular heterogeneity and lineage specification. Integrative multi-omics approaches, combining transcriptomics, proteomics, and epigenomics uncover complex regulatory networks in which miRNAs interact with other non-coding RNAs and signaling pathways. Artificial Intelligence (AI) -driven analytics enhance the discovery of biomarkers and therapeutic targets, offering precision strategies for clinical and livestock applications. miRNA profiling now informs breeding strategies to improve cashmere fiber quality and is a minimally invasive diagnostic tool for hair disorders. We outline future directions, including improved miRNA delivery methods, systems biology integration, and AI-powered multi-omics approaches to deepen our understanding of hair follicle biology and facilitate practical applications in medicine and agriculture.